Accessibility to credit of small medium enterprises in Vietnam. (2016) - Dao, Ha Thi Thieu; Mai, Nguyen Thi; Kim, Nguyen Thien
The growth prospects of a SME highly depend on its potential to invest in restructuring and innovating, which in turn, needs capital. Access to financial resources, therefore, becomes a significant factor of the growth of a SME as well as economic growth in developing countries. This paper examines determinants of credit accessibility of SMEs in Vietnam. Both quantitative and qualitative approaches are applied, in which logit model is employed to investigate possibility of credit accessibility of 756 SMEs in Vietnam. Also, a semi-structured questionnaire is used to investigate the causes of poor connections between SMEs and banks in Ben Tre province. The results express that the factors including education of enterprises' managers, collaterals and asset values of enterprises, loans of enterprises taken from Vietnam Bank for Social Policies (VBSP), state banks or even private banks and the distances between enterprises and credit institutions will increase the probability of credit accessibility of SMEs. A number of recommendations are introduced to promote the credit accessibility of SMEs such as providing unsecured loans and cooperating loans, improving the roles of state banks of Vietnam and decreasing the regional differences.